The Effect of Dendrophthoe pentandra (L.) Miq Ethanol Extract on Malondialdehyde (MDA) in Hyperglycemic Rats - Syafitri, Anggun; Yuandani, Yuandani; Widyawati, Tri (International Journal of Science, Technology & Management, 2023)
Dendrophthoe pentandra (L.) Miq is a parasitic plant with medicinal potential found in 3000 other plant species. The duku parasite is usually considered a parasite on the duku plant and is often discarded because it is thought to interfere with the growth of the duku plant. The purpose of this study was to see the effect of the duku parasite leaf extract on the reduction of malondialdehyde (MDA) in hyperglycemic rats. MDA levels were measured by thiobarbituric acid-reactive substance (TBARS) assay with doses of duku mistletoe leaf ethanol extract of 400, 200, and 100 mg/kg BW. MDA levels were analysed using rat blood plasma, which was measured using a spectrophotometer at a wavelength of 532 nm. Oral administration of EEDBD 400, 200, and 100 mg/kg BW reduced MDA levels in hyperglycemic rats. However, only EEDBD 400 mg/kg BW showed a significant difference between the negative control (CMC-Na), but with glibenclamide and the normal groups, there was no significant difference.